Concrete Production and Curing with Recycled Wastewater: A Review on the Current State of Knowledge and Practice - Tobby Michael, Agwe; Philip, Tibenderana; Moses N, Twesigye-Omwe; Joel Webster, Mbujje; Abdulkadir, Sholagberu Taofeeq (Hindawi, 2023)
A number of factors have combined to put excessive pressure on the finite available freshwater resources. These include increasing population, rapid urbanization, industrialization, changed land pattern usage and land cover, change in the overall ecological system, and increased temperature and unscientific compromises in the extraction of water are at alarming threshold putting pressure on the finite available freshwater resources. As a result, many countries have been stressed or are at the verge of being stressed. The problem is worsened day by day by prolonged drought, unchecked discharge of untreated or partially treated wastewater to the freshwater reservoirs and lack of proper water quality control measures and management. Many initiatives such as Zero Liquid Discharge of industrial wastewater into freshwater bodies such as reservoirs, lakes, and ponds, and the use of recycled wastewater for irrigation and domestic purposes have started to be embraced as measures to put a check on the fast depleting freshwater resources for sustainable socio-economic development. The construction industry is the second largest consumer of freshwater just after agriculture. Concreting alone consumes, annually, over one trillion m3 of freshwater globally while the concept of the use of wastewater and/or recycled water in the concrete-making processes is yet to be adopted. Hence, this paper presents a general review of the current state of knowledge and practice on concrete production and curing using recycled wastewater from industrial, commercial, and domestic activities. An extensive review of the existing literature revealed that recycled water is fit for concrete production and curing purposes. The observations made are based on the assessment of wastewater quality parameters and their impacts on some selected concrete properties such as initial setting time and compressive strength. Due to scanty research on the impacts of varying concentrations of different ingredients in any questionable water on selected properties of reinforced concrete and its durability, thus, further research is recommended.